2020
DOI: 10.1038/s41467-020-17293-3
|View full text |Cite
|
Sign up to set email alerts
|

Th1 responses in vivo require cell-specific provision of OX40L dictated by environmental cues

Abstract: The OX40-OX40L pathway provides crucial co-stimulatory signals for CD4 T cell responses, however the precise cellular interactions critical for OX40L provision in vivo and when these occur, remains unclear. Here, we demonstrate that provision of OX40L by dendritic cells (DCs), but not T cells, B cells nor group 3 innate lymphoid cells (ILC3s), is critical specifically for the effector Th1 response to an acute systemic infection with Listeria monocytogenes (Lm). OX40L expression by DCs is regulated by cross-tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…Full CTL activation, accumulation and survival is influenced by a wide range of factors, including co-stimulatory molecules such as CD80/86, CD137, CD70, and OX40, as well as inflammatory cytokines and cytokine mediated proliferation [35][36][37][38] . Furthermore, the local chemokine and cytokine environment in secondary lymphoid organs, immunosuppressive cells and cytokines which reduce T cell responses, as well as T cell promiscuity, crossreactivity, and differences between murine and human immunology all add further complexity to such predictions 9,[39][40][41][42][43][44] . Therefore, a peptide sequence and their physicochemical properties are not the only contributors to effective immunogenicity and these factors are not yet included in existing models.…”
Section: Discussionmentioning
confidence: 99%
“…Full CTL activation, accumulation and survival is influenced by a wide range of factors, including co-stimulatory molecules such as CD80/86, CD137, CD70, and OX40, as well as inflammatory cytokines and cytokine mediated proliferation [35][36][37][38] . Furthermore, the local chemokine and cytokine environment in secondary lymphoid organs, immunosuppressive cells and cytokines which reduce T cell responses, as well as T cell promiscuity, crossreactivity, and differences between murine and human immunology all add further complexity to such predictions 9,[39][40][41][42][43][44] . Therefore, a peptide sequence and their physicochemical properties are not the only contributors to effective immunogenicity and these factors are not yet included in existing models.…”
Section: Discussionmentioning
confidence: 99%
“…Th1 differentiation was also attenuated in a systemic Listeria monocytogenes infection model of OX40-deficient mice. NK cellderived interferon-γ upregulates OX40L expression in dendritic cells, and OX40L-expressing dendritic cells are critically involved in OX40+ Th1 cell expansion in this model [23]. Interestingly, OX40L-expressing group 3 innate lymphoid cells (ILC3s), but not dendritic cells, were required for full Th1 cell differentiation in an intestinal Salmonella infection model, suggesting that different APC population may be crucial for OX40L-dependent, site-specific inflammation [23].…”
Section: Ox40-ox40l Axis In Type 1 and Type 2 Immune Responsesmentioning
confidence: 97%
“…OX40 is expressed in activated effector T and effector memory T cells. Its stimulation promotes and sustains T helper 1 (Th1) and Th2 activation rather than B cell responses [10,11,22,23] (Figure 2).…”
Section: Ox40-ox40l Axis In Type 1 and Type 2 Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The OX40 stimulation activates NF-κB pathway, which indirectly increases expression of apoptosis-suppressing proteins prolonging cell survival, and the activated T-cell nuclear factor (NFAT) pathway that leads to an increase in the synthesis of cytokines such as IL-2, IL-4, IL-5, and IFN-γ ( So and Croft, 2007 ). Although, some data suggest the importance of OX40/OX40L signaling for primary and memory T H 2 response ( Salek-Ardakani et al, 2003 ; Jenkins et al, 2007 ; Pattarini et al, 2017 ), there are also evidences that OX40 costimulation plays an important role in the T H 1 response ( Weinberg et al, 1999 ; De Smedt et al, 2002 ; Gajdasik et al, 2020 ). Therefore, it was observed that OX40 costimulation may enhance both a T H 1 and a T H 2 response without supporting the role for switching polarization of CD4 + T cells ( De Smedt et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%